How Wage Announcements Affect Job Search: A Field Experiment - Michèle Belot; Philipp Kircher; Paul Muller (Institute of Labor Economics (IZA), 2018)
We study how job seekers respond to wage announcements by assigning wages randomly to pairs of otherwise similar vacancies in a large number of professions. High wage vacancies attract more interest, in contrast with much of the evidence based on observational data. Some applicants only show interest in the low wage vacancy even when they were exposed to both. Both findings are core predictions of theories of directed/competitive search where workers trade off the wage with the perceived competition for the job. A calibrated model with multiple applications and on-the-job search induces magnitudes broadly in line with the empirical findings.
Keywords: J31; J63; J64; C93; 330; online job search; directed search; wage competition; field experiments